2022
DOI: 10.3390/nano12030310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application of ZnO Nanoparticles on Lentil Production, Stress Level and Nutritional Seed Quality under Field Conditions

Abstract: Nanotechnology offers new opportunities for the development of novel materials and strategies that improve technology and industry. This applies especially to agriculture, and our previous field studies have indicated that zinc oxide nanoparticles provide promising nano-fertilizer dispersion in sustainable agriculture. However, little is known about the precise ZnO-NP effects on legumes. Herein, 1 mg·L−1 ZnO-NP spray was dispersed on lentil plants to establish the direct NP effects on lentil production, seed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 66 publications
(94 reference statements)
0
4
0
1
Order By: Relevance
“…In a very short amount of time, perovskites solar cells (PSCs) have attracted the attention of the photovoltaic industry by providing a solar-to-electric power conversion efficiency (PCE) rate greater than 23%. Currently, it is a potential candidate among commercially available solar cells, and nanomaterials play the main role in their efficiency [ 1 , 2 , 3 , 4 , 5 , 6 ]. Inorganic–organic hybrid perovskites of metals halides have a general formula: ABX 3 , where the A-site is composed of organic cations that usually consist of MA + (CH 3 NH 3 + ), Cs + , and FA + [(NH 2 ) 2 CH] + ions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In a very short amount of time, perovskites solar cells (PSCs) have attracted the attention of the photovoltaic industry by providing a solar-to-electric power conversion efficiency (PCE) rate greater than 23%. Currently, it is a potential candidate among commercially available solar cells, and nanomaterials play the main role in their efficiency [ 1 , 2 , 3 , 4 , 5 , 6 ]. Inorganic–organic hybrid perovskites of metals halides have a general formula: ABX 3 , where the A-site is composed of organic cations that usually consist of MA + (CH 3 NH 3 + ), Cs + , and FA + [(NH 2 ) 2 CH] + ions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, identical FE-SEM images of gold nanoparticles prepared by the green synthesis technique have been reported [39]. Gold nanoparticles synthesized by the green method at room temperature, where the majority of the particles seem spherical, have also been reported in the near past [40].…”
Section: Field-emission Scanningmentioning
confidence: 80%
“…El-Bassiouny et al (2022) concluded that wheat plants treated with ZnO-NPs maximized all the studied growth parameters, biochemical direction, and yield. Kolenˇcík et al (2022) proved that treatment with nano ZnO promoted yield, 1000-seed weight, and the pod number per plant. Hussain et al (2019) revealed that treatment with different Zn sources induced maximum values of wheat plants' dry matter, crude protein, fiber, gluten, and mineral contents.…”
Section: Introductionmentioning
confidence: 93%